Final Adult Height in Girls Treated with GnRH Analogues for Precocious Puberty Around Age Eight - Semra Bahar Akın; İlker Tolga Özgen (Children, 2025)
Introductions: Precocious puberty initiated at a very young age causes a severe loss in height potential and should be treated with gonadotropin-releasing hormone agonists (GnRHa). Controversial findings exist regarding the efficacy of GnRHa treatment in girls with central precocious puberty (CPP) onset around the age of 8. This research assessed the impact of GnRHa treatment on the final height (FAH) of 117 girls diagnosed with CPP within this age group. Methods: This retrospective study included 117 CPP girls diagnosed at around age 8 (7–9 years old). Girls who started treatment between the ages of 8 and 9 (n = 71) and 7 and 8 (n = 46) were divided into groups 1 and 2, respectively. Predicted height (PAH), target height (TH), and FAH were calculated from medical records. Girls’ PAH, TH, and FAH were also compared between groups. Results: At beginning of treatment, the girls’ average ages were 8.59 ± 0.27 in group 1 and 7.50 ± 0.47 in group 2. In groups 1 and 2, GnRHa therapy durations were 1.97 ± 0.54 and 2.91 ± 0.61, respectively. There were no significant differences in TH (160.53 ± 5.49 vs. 160.57 ± 4.94), PAH (158.72 ± 5.23 vs. 158.35 ± 5.57), and FAH (162.42 ± 5.32 vs. 162.14 ± 5.70) between groups. FAH improved 4 cm from PAH in both (p = 0.001). Multivariate linear regression analysis showed that baseline height SDS was the main FAH predictor (Beta: 0.572, p = 0.001). Conclusions: GnRHa may improve FAH even if the treatment is delayed after age 8. However, as this improvement is limited for this age group, the therapy option should be individualized and should not be considered for all children.